What social determinants will cause ethical challenges in geriatric care? Comments from South Africa - Laetus Lategan; Gert van Zyl; Willem Kruger (Journal of Public Health in Africa, 2023)
Background: Social determinants are defined as those nonmedical factors that influence health. Their influence is especially evident in vulnerable communities, such as the geriatric one. However, which social determinants will cause ethical challenges in geriatric healthcare in South Africa are not yet confirmed.